Short-term ingestion of sublethal microcystin levels disrupts stress response in male mice - Salan Ghaju; Evance Pakuwal; Rafaela S. C. Takeshita; Rafaela S. C. Takeshita; Xiaozhen Mou; Xiaozhen Mou; Wilson C. J. Chung; Wilson C. J. Chung (Frontiers in Endocrinology)
Cyanobacterial harmful algal blooms (cHABs) produce various cyanotoxins, primarily microcystin leucine arginine (MC-LR). Studies demonstrated that intraperitoneal delivery of high-dose MC-LR affects the rat stress response, which is regulated by the hypothalamus-pituitary-adrenal (HPA) axis. In general, during stress parvocellular neurons in the hypothalamic paraventricular nucleus (PVN) secrete corticotropin-releasing hormone (CRH), triggering adrenocorticotropic hormone (ACTH) release from the anterior pituitary, which leads to increased cortisol in humans and corticosterone in rats and mice. Here, we tested the hypothesis that short-term sublethal ingestion of MC-LR activates the peripheral and central components of the HPA axis. First, we found that young adult male mice gavaged with MC-LR (50 μg/kg bw, p.o.) every 2 days for 21 days had elevated plasma corticosterone levels when compared to H2O (vehicle) mice. Ingestion of contaminated fresh water is a likely natural route of MC-LR exposure for animals, including humans. Second, Crh and arginine vasopressin (Avp) mRNA expressions were elevated in the hypothalamus of MC-LR-dosed mice. Third, ΔFOSB (i.e., long-term cell activity marker) immunofluorescence in the PVN and hippocampal dentate gyrus (DG) of MC-LR mice was significantly elevated compared to vehicle mice, but not in cornu ammonis (CA) 1, 2 and 3. In contrast, MC-LR mice had reduced hypothalamic glucocorticoid receptor (Gr) mRNA expression. Fourth, no significant changes were found in the mRNA expression of the inflammatory markers: tumor necrosis factor α (Tnf-α) and interleukin-1β (IL-1β) in the hypothalamus, liver, and spleen and C-reactive protein (Crp) in the liver and spleen. These data indicate that short-term ingestion of sublethal levels of MC-LR resulted in increased peripheral and central HPA axis activity.